Occurrence of new case-bearer on cereals, Coleophora perplexella Toll, 1960 (Lepidoptera: Coleophoridae) - D. Haouas; G. Baldizzone; A. Hamdi; C. Hafsi; M. Ben-Hammouda (SHILAP)
Coleophora perplexella Toll, 1960 it is native of Spain and Portugal, but it has detected out of its origin area, and was found in Sardinia, Morocco and Algeria without its host plant being identified. Recently has been observed in France (Toulon) on Hordeum murinum L. and Bromus sterilis L. (Poaceae). However, it was never cited among the Tunisian entomofauna. In addition, C. perplexella was never known as agricultural pest in its area or elsewhere. Moreover, no deep studies diagnosis and biology were conducted. This paper is a first study on C. perplexella, detected as an agricultural pest on oat (Avena sativa L., 1753) and barely (Hordeum vulgare L., 1753) making serious damages on early seedlings. Besides, a description and illustrations of different biological stage was provided. Results highlight a difference between the appearance dates of emerged new adults under both controlled and ambient conditions. According these results we can conclude on adaptation plasticity to the environmental conditions. In fact, C. perplexella can survive and cause damage at temperature between 7-10º C from December to February, and 23-25º C of controlled conditions.